Tính lý thuyết trường sóng địa chấn trong vỉa than trên mô hình toán - Vinh, Nguyễn Đức; Thăng, Nguyễn Công (Journal of Computer Science and Cybernetics, 2016)
This paper presents algorithms and results of calculation of seismic wave field in mine layer on mathematical models.